Surface properties and in-vitro bioactivity studies of TiO2 nanowire doped transition metal (M=Fe, Co, and Mn) - MISRIYANI, Misriyani; ENAYAH, Enayah; TIAN, Z. Ryan; ILHAMJAYA, Andi Meutiah (Journal of Metals, Materials and Minerals, 2026)
This study investigates the influence of transition metal (Fe, Co, Mn) doping on the surface properties and in-vitro bioactivity of TiO2 nanowires. It aims to elucidate how transition-metal doping alters the surface behavior and biological response of TiO2 nanowires, enabling their potential use in biocompatible and magnetically responsive materials. Magnetic TiO2 nanowires doped with transition metals (Mx+/TiO2) were successfully prepared by a hydrothermal method using titanium dioxide in alkaline solution. Cations were added with Ti/Mx+ molar ratios of 5 to produce Fe/TNW, Co/TNW, and Mn/TNW. Characterization using SEM and XRD determine their surface properties. In-vitro bioactivity tests were conducted by observing the response of C2C12 cells. A cytotoxicity assay determined the effect of TiO2 Nanowires (5 mg∙mL‒1) on C2C12 cell viability at 48 h and 72 h. The results showed that metal-doped TiO2 nanowires did not significantly affect cell activity, and C2C12 cell differentiation remained. In conclusion, transition metal-doped TiO2 nanowires do not affect C2C12 cell activity at certain doses. The magnetic properties of doped TiO2 nanowires open new opportunities for controlled drug delivery using external magnets.